Association Between Home Physical Environment, Individual Characteristics and Personal Hygiene and the Incidence of Leprosy in Cirebon Regency - Irene Silitonga; Nurjazuli Nurjazuli; Sulistiyani Sulistiyani; Budiyono Budiyono; Suhartono Suhartono (Universitas Islam Negeri Sumatera Utara, Medan, 2026)
Leprosy is a contagious disease caused by the bacterium Mycobacterium leprae, which attacks the peripheral nerves and skin. This study aims to analyze whether household ventilation, housing density, window availability, wall and floor conditions, room separation, and personal hygiene behaviors are significantly associated with leprosy incidence in Cirebon regency. This research is an analytical observational study with a case-control design, involving 77 case respondents and 77 controls randomly selected. Data were collected through observation and interviews regarding home conditions and personal habits, and then analyzed using the chi-square test. The results show that the variables of ventilation size (p-value < 0.001 and OR = 5.361), window condition (p-value < 0.001 and OR = 3.640), room separation (p-value < 0.001 and OR = 6.249), and occupancy density (p-value = 0.014 and OR = 2.387) were significantly associated with the incidence of leprosy, while floor type (p-value = 0.297 and OR = 1.539) and wall type (p-value = 0.250 and OR = 1.543) were not associated with leprosy incidence. Regarding personal hygiene factors, knowledge (p-value < 0.001 and OR = 7.125), attitude (p-value < 0.001 and OR = 6.818), shared towel use (p-value < 0.001 and OR = 5.2), and nail-cutting habits (p-value < 0.001 and OR = 3.433) had a significant effect on leprosy, while bathing frequency (p-value = 0.294 and OR = 1.539) did not show a significant relationship. The findings indicate that the physical housing environment and personal hygiene are associated with leprosy occurrence in Cirebon Regency, suggesting that control efforts should prioritize housing improvements and the promotion of proper hygiene practices Keyword: Leprosy, Physical Home Environment, Knowledge, Attitude, Personal hygiene